Pemanfaatan Ampas Kopi dan Tepung Beras Menjadi Masker Organik - Nurfadilah, Dila; Yusriah, Nuri; Dewi, Riska; Iqomul Haq, Muhammad Rosyad; Nur Rahmat, Luqman; Abdul Rozak, Rama Wijaya; Sugiarti, Yatti (Jurnal Sosiologi Pertanian dan Agribisnis, 2023)
Indonesia is an agricultural country with one of its sub-sectors being plantations and coffee being one type of plantation crop that has long been cultivated. This has resulted in a high culture of drinking coffee resulting in an increase in coffee grounds. There are still many coffee shops/cafes that throw away coffee grounds, even though coffee grounds can still be utilized, one of which is as an organic face mask. Coffee grounds contain antioxidants that can maintain skin health, moisturize and smooth the skin. The purpose of this study is to utilize coffee grounds and reduce environmental pollution which causes the greenhouse effect and to find out how many people like organic face masks from coffee grounds and rice flour. In this study, the face mask was made with a formulation of 50% coffee grounds and 50% rice flour. The test parameters in this study are organoleptic tests of aroma, color, texture, liking, pH test and effectiveness test. The results showed an average pH value of 5.0. The average color organoleptic test was 2.52, texture 2.88, aroma 3.32 and average liking 3.2. The drying time of the mask is 15 minutes. This coffee grounds face mask is well accepted by panelists.